Absolute Iron Deficiency in Children: Review - Talarico, Valentina; Galati, Maria Concetta; Saracco, Paola; Raiol, Giuseppe; Miniero, Roberto (International Journal of Pediatrics and Child Health, 2022)
Absolute iron deficiency (A-ID) is still the most common form of malnutrition and iron deficiency anemia (A-IDA) is the most frequent kind of anemia among children/adolescents in developed countries. Prematurity, decreased dietary source, malabsorption and blood loss represent the prevalent causes of iron deficiency. A-ID and A-IDA will present with a wide variety of symptoms involving multiple organs and systems. Recent literature highlights the association between chronic A-ID and possible delayed motor, cognitive development and decreased cognitive performance. Oral iron administration remains the main treatment. The dose of elemental iron is 2–6 mg/kg/day; recent reports demonstrate that iron administration every other day is equally effective at the doses administered daily with fewer side effects. When normal Haemoglobin (Hb) values are reached, treatment must be generally continued for 3 months in order to replenish iron stores. Rarely intravenous iron administration may be necessary in some selected patients; and the new commercial products based on parenteral iron have shown a good safety profile. Prevention of A-ID might be considered as an important issue of public health.